(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2024)
Niger (Guizotia abyssinica) plants are cultivated in various parts of Ethiopia. However, there are no investigation on physical properties of oil extracted from niger and its yield. The current work investigated the yield and physicochemical analysis of oil extracted from it. The extracted oil amount (40%) is good when compared to the reported Ethiopian Niger seed oil yields. The physicochemical analyses of the oil were determined according to the standard procedures. Among the determined properties of the seed oil were moisture content (9.5 ± 0.40%), specific gravity at 250, (0.90 ± 0.02), acid value (1.20 ± 0.50 mg KOH/g oil), saponification value (175.0 ± 0.60 mg KOH/g oil), free fatty acid content (0.60 ± 0.25%), and ester content (173.8 ± 0.10 mg KOH/g oil). In conclusion, on the basis of investigated physicochemical properties it indicates that the oil extracted from seeds of G. abyssinica is a good quality of oil and have dietary recommendations. Bangladesh J. Sci. Ind. Res. 59(2), 67-72, 2024